THE EFFECT OF INTEGRITY, WORKLOAD, AND COMPETENCE ON THE PERFORMANCE OF BOS FUND MANAGERS OF STATE HIGH SCHOOL AND VOCATIONAL SCHOOL IN BATAM CITY WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Astri Dhanarizki; Bambang Satriawan; Sri Yanti (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of integrity, workload, and competence on the performance of School Operational Assistance (BOS) Fund managers at public senior high schools (SMA) and vocational high schools (SMK) in Batam City, with organizational commitment as an intervening variable. The research method used is a quantitative method with a survey approach. The study population includes all BOS Fund managers at public senior high schools (SMA) and vocational high schools (SMK) in Batam City, while the sample was determined using a purposive sampling technique. Data collection was carried out through a questionnaire that has been tested for validity and reliability. Data analysis used a structural equation model (SEM) based on Partial Least Squares (PLS) to test the direct and indirect effects between variables. The results show that integrity, workload, and competence have a significant effect on performance, both directly and through organizational commitment. This finding implies that increasing integrity, proportional workload management, and developing the competence of BOS Fund managers can improve their performance, especially if supported by strong organizational commitment.